The Philosophical Disenfranchisement of Art - Danto, Arthur C. 1924-2013 (New York Columbia University Press, 1986)
In this acclaimed work, first published in 1986, world-renowned scholar Arthur C. Danto explored the inextricably linked but often misunderstood relationship between art and philosophy. In light of the book's impact -- especially the essay "The End of Art," which dramatically announced that art ended in the 1960s -- this enhanced edition includes a foreword by Jonathan Gilmore that discusses how scholarship has changed in response to it. Complete with a new bibliography of work on and influenced by Danto's ideas, The Philosophical Disenfranchisement of Art continues to be of interest to anyone who thinks seriously about art, as well as to philosophers, aestheticians, and art historians.
Keywords: 20th Century (1901-2000); Esthetics